Exploring the process and challenges of Indonesian education students in the use of Canva media in project-based learning - Alwa, Fahma Aisyah Putri; Maulana, Khalisa Kadhia; Bahriya, Silvi; Hindun, Hindun (Priviet Social Sciences Journal, 2025)
This study aims to explore the processes and challenges experienced by students of the Indonesian Education study program in utilizing Canva as a learning medium in PjBL. This research uses a descriptive qualitative research method with thematic interviews and data analysis techniques. This research not only explores the processes and challenges but also relates to the TPACK framework. The results show that students have been familiar with Canva since high school and that the frequency of use increases as the semester rate increases. Canva's use of media is considered to help in planning creative, efficient, and collaborative project outcomes. However, several challenges in its use still arise, especially those related to unstable Internet connections, weak coordination between group members, and limited premium access. These findings confirm that the use of Canva not only enriches students' learning experiences but also demonstrates the integration of technology, pedagogy, and content elements as described in the Pedagogical Knowledge and Technology Content (TPACK) framework. Through this integration, students learn to balance technological skills with pedagogical understanding and learning materials. Overall, Canva's implementation in PjBL contributes to strengthening 21st-century skills such as critical thinking, collaboration, communication, and digital literacy. This study recommends increasing digital infrastructure support and learning technology training for students so that the use of Canva in PjBL can be more optimal and sustainable.